Ο ναός του Αγίου Νικολάου στο ρέμα του Σωφρόνη Λακωνίας - ΚΑΠΠΑΣ, Μιχάλης (Byzantina Symmeikta, 2012)
The church of Hagios Nikolaos at Sofronis gorge, Laconia At the southwest slopes of mount Parnon, on the lower part of the Tzitzina gorge, lays the church of Hagios Nikolaos, the catholicon of an old monastery, today in ruins. Close to the church there is a spring of clear water, known to the locals as the Sofronis spring; the gorge itself, from that level until the point that it reaches the Kelefina river, some kilometers lower, is known by the name “Sofronis gorge”. The catholicon is a cross-in-square church of the variant with shorter west arm, with a narthex and an exonarthex at the west part of the nave. The west arm of the cross and the lateral corner bays are much shorter than the corresponding east parts, which makes the west corner bays look like blind arches. Above the central square bay of the nave lays a peculiar dome, whose drum is cylindrical inside, while outside it has a rectangular shape ending in triangular gables at its east and west side. The esonathex was initially cross-vaulted, completely unified with the main church. Its central bay was covered by a longitudinal barrel vault at the same level as the arch of the west cross arm of the nave. The west sides of its corner bays are articulated by two blind arches, of which the north one might have been used as a burial arcosolium. A small niche is formed at the east wall of its south corner bay, either for liturgical function or to be used for the service of the holy water. The exonarthex has a complicated structural history. Initially was timber-roofed, while in a later phase it was covered by a transverse barrel vault, for whose support blind arches were constructed at its west side, now in ruins. The external surfaces of the church are plain, without any kind of articulation, as was the rule in monuments of southern Greece. The walls were constructed by roughly hewn stones with plenty of brick fragments in the joints. At least one level of wooden ties strengthens the walls in the springing line of the vaults. The cross arms of the nave were covered by saddle tile roofs, as was the rule in cross-in-square churches of the byzantine periphery. The east corner bays where roofed at a lower level with lean-to roofs with north and south direction respectively. The west corner bays on the other hand, were so much thinner that it was rather impossible to have independent roofing. In that case, the roofs of the lateral compartments of the esonarthex gave externally the impression of west corner bays. This peculiar arrangement, emphasizing the unification between the nave and the esonathex, is very rarely attested among the known examples of cross-in-square churches with shorter west arm, relating the church at the Sofronis Gorge with a small group of relevant monuments (Fraggavilla, Klesa-Porti). The form of the dome of the church in question must not be confused with the similarly shaped raised central bays in transverse barrel vaults. Thought there are a few similarities with a small number of byzantine and post byzantine domes, it seems that the dome of Hagios Nikolaos at Sofronis Gorge is unique in the ecclesiastical architecture of Byzantium, most likely the result of an improvisation of a local group of masons. Hagios Nikolaos was initially decorated with frescoes, fragmentarily preserved. Three different phases can be distinguished due to stylistic and iconographic criteria. The first one is very difficult to be studied because of its poor condition of presentation. The second one can be dated to the late thirteenth century, while the last one might be placed in the fifteenth century. It is difficult to conclude to an exact dating for the church of Hagios Nikolaos, because of the lack of documentary and epigraphic evidence. Based on its morphological and typological features a rather broad dating between the eleventh and twelfth centuries seems possible for the monument in examined. Hagios Nikolaos at the Sofronis Gorge, though not an impressive building, provides valuable input to the study of the ecclesiastical architecture in Laconia during the Middle Byzantine Era, a period whose surviving monuments in this part of the Peloponnese are very scarce. Hagios Nikolaos is valuable for another reason as well: it seems to be the oldest monument at the Sofronis Gorge and its adjacent area, where a great number of monastic foundations are gathered, still inadequately studied.